THE DIGITAL SUBLIME: algorithmic binds in a living foundry. Issue 3 (3rd May 2020) - Bennett, Gaymon
Abstract: This article explores the critical limitations of the now decades-long shift toward digital culture in the material and cultural constitution of biotechnology. It does this by telling the story of three contemporary efforts to reimagine the logic of life on the logic of the digital and the struggles attendant to building the infrastructures needed to actualize that re-imagination and make it profitable. In tracing these stories, it lifts out how biotechnologists, once caught in the spell of the digital sublime, are having to confront the ways in which dreams of a data-driven and automated biology, far from eliciting an exalted future of health, wealth, and security, are simply reinforcing at the level of the organism a world already boxed in by algorithmic modes of reason and governed by imperatives of optimization. In the midst of these binds, this article points to a pathos which is beginning to stir at the bench as blue-collar technologists seek to activate an older feel for craftwork, and how this pathos signals a familiar but vital reciprocity between the maker and the made. It concludes that, in the end, breakdowns in the digital sublime make space for a more interesting biotechnical proposition, one in which the living thing being crafted has to be accommodated rather than rendered algorithmic: the cellular targets of biotechnical intervention must be coerced, cajoled, and enticed into playing along with our biotechnical imaginations. To act differently proves to be the real source of our trouble. The stories in this article draw on fieldwork conducted by the author through multiple experiments in collaborative anthropology. These experiments began in connection to a then-emerging brand of biotechnology called synthetic biology, were carried forward in view of a "post-engineering" approach to systems biology, and are currently (as of the writing of this essay) being conducted among biologists and technologists working to build "digital infrastructures" for the life sciences (i.e., digital tools for assembling, mediating, and synthesizing post-genomic biology).